Ownership structure, related party transactions, and firm valuation : evidence from Indian business groups - Khosa, Amrinder; Ahmed, Kamran; Henry, Darren (Cambridge : Cambridge University Press, 2019)
Concentrated ownership is considered to be the best protection for shareholders in economies where legal protection is relatively weak. This book investigates and concludes, for Indian business groups, that concentrated-inside ownership provides opportunities for the expropriation of minority shareholders. While more concentrated direct ownership of controlling families results in a higher market value of equity, indirect ownership obtained through cross-holding provides incentives to extract private benefits and results in value loss. This finding requires the prompt attention of regulatory bodies, outside investors and other interested parties. This book examines the effect of ownership structure and disclosure of related-party transactions on firm valuation of group-affiliated firms in India, by using a sample of 317 listed firms comprising 1350 firm-year observations from 2008 to 2017. Well-accepted value-relevance models are employed to examine the effect of ownership rights on market value of equity and valuation effect of RP trading, asset transfer, investment and loan transactions.
Title from publisher's bibliographic system (viewed on 24 Apr 2019).
Keywords: Corporate governance -- India; Family-owned business enterprises -- India -- Management; Corporations -- India -- Finance